2021
DOI: 10.1371/journal.pone.0252054
|View full text |Cite
|
Sign up to set email alerts
|

Body size ideals and body satisfaction among Dutch-origin and African-origin residents of Amsterdam: The HELIUS study

Abstract: Objective Obesity is highly prevalent among ethnic minorities and acceptance of larger body sizes may put these ethnic minorities at risk of obesity. This study aimed to examine body size ideals and body satisfaction in relation to body weight, in two Sub-Saharan African (SSA)-origin groups in the Netherlands compared to the Dutch. Additionally, in the two SSA-origin groups, this study assessed the mediating role of acculturation in the relation between ethnicity and body size ideals and body satisfaction. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Previous research has suggested that social body weight norms may differ between immigrants and natives as well as between ethnic groups within countries. 25 For the present study, we further focused on the larger subsample of White Americans and excluded subsamples of immigrants and other ethnic groups because of small number of cases.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Previous research has suggested that social body weight norms may differ between immigrants and natives as well as between ethnic groups within countries. 25 For the present study, we further focused on the larger subsample of White Americans and excluded subsamples of immigrants and other ethnic groups because of small number of cases.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Finally, all other categories of relational/attributional factors in Figure 1 have been shown to be important, either in explaining inequalities in health between the ethnic minority groups and the population of Dutch descent, or in identifying variation in health within the ethnic minority populations. Examples of the former include ethnic differences in genetic profile and associations with pro-diabetogenic lipid profile (95) and the gut microbiome (96), and acculturation variables explaining variation in dietary patterns (97) and in body size ideals (98).…”
Section: Explaining Inequalitiesmentioning
confidence: 99%
“…Satisfaction with body weight was measured as the degree of concordance between ideal BMI and current BMI, calculated from self-reports of weight and height using the standard BMI formula (3,21). Previous research has validated the difference between ideal and current BMI as a measure of dissatisfaction with weight, although the validation analyses were limited to young age (22).…”
Section: Satisfaction With Body Weightmentioning
confidence: 99%